Physical exercise and self-esteem in women facing lockdown-related domestic violence - Legrand, Fabien D. (Journal of family violence, 2022)
The purpose of the present brief report was to examine the effects of a 6-week long physical exercise program on global self-esteem and physical self-perceptions among women who faced lockdown-related domestic violence. Thirty-six domestic violence victims (mean age: 33.4 ± 3.5 yrs-old) were enrolled in this study. Participants were randomly and equally assigned to two intervention (physical exercise, counseling/support group therapy) and one control (no intervention) groups. The French version of the Physical Self-Perception Profile (ISP-25) was administered to all participants pre- and post-study. Mixed-design ANOVAs revealed significant Group by Time interactions for Global Self-Esteem, Physical Condition, and Body Attractiveness. Global Self-Esteem significantly improved in the two intervention groups, with a trend for better improvement in women who exercised compared to those who took part in support group meetings, Cohen’s d = 0.68, 95% confidence interval [‒0.18, 1.54]. On the other hand, only women from the Physical Exercise group reported significant gains in Physical Condition and Body Attractiveness. There was no change in any of the assessed variables for women in the control group. The present study provides new insights on the role of physical exercise in the understudied population of women with domestic violence. Our findings are discussed and related to previous studies.